"To me, you are not a Serb": Ethnicity, ambiguity, and anxiety in post-war Sarajevo. (June 2020) - Golubović, Jelena
The siege of Sarajevo has altered the experience of ethnicity, reconfiguring ethnic categories into moral boundaries. From 1992 to 1995, the city was held under siege by the Army of Republika Srpska, and many Sarajevan Serbs still grapple today with the feeling that others view them as aggressors. Based on one year of ethnographic fieldwork with Serb women of the pre-war generations, I describe how they intentionally make small alterations in gesture and body language in order to perform ethnic ambiguity, and avoid being read by others as Serb. While anthropological accounts have tended to use performativity to emphasize the constructed and situational nature of ethnicity, here I focus on the anxiety that drives Serb women's performances in order to capture the inherent and inescapable feeling of ethnicity in a post-war space. I also discuss the difficulty of capturing this anxiety through empirical methods, navigating the discrepancy between Serb women's narrative accounts of ethnic stigmatization compared to the apparently unproblematic flow of everyday social life. Through this discrepancy, I demonstrate how the embodied and ever-accumulating feeling of ethnic anxiety can conjure threats where there may be none, and how it can charge even the most (seemingly) mundane encounters.